ON THE COMPLEXING ABILITY OF ERIOCHROME BLACK T AS A METALLOCHROMIC INDICATOR FOR SOME ALKALI AND ALKALINE EARTH CATIONS IN ACETONE AND DIMETHYLSULPHOXIDE SOLUTIONS (Journal of Sciences, Islamic Republic of Iran)
The interaction between eriochrome black T and Li , Na , K ,Mg and Ca ions in acetone and dimethylsulphoxide solutions has been investigated spectrophotometrically. The formation constants of the resulting 1 : 1 complexes were determined and found to decrease in the order Mg >Ca >Li >K >Na in both solvents used. There is an inverse relationship between the stabilities of the complexes and the solvating ability of the solvents